RNA stem-loop to G-quadruplex equilibrium controls mature MicroRNA production inside the cell - Pandey, Satyaprakash; Agarwala, Prachi; Jayaraj, Gopal Gunanathan; Gargallo, Raimundo; Maiti, Souvik (Biochemistry, 2015)
The biological role of the existence of overlapping structures in RNA is possible yet remains very unexplored. G-Rich tracts of RNA form G-quadruplexes, while GC-rich sequences prefer stem-loop structures. The equilibrium between alternate structures within RNA may occur and influence its functionality. We tested the equilibrium between G-quadruplex and stem-loop structure in RNA and its effect on biological processes using pre-miRNA as a model system. Dicer enzyme recognizes canonical stem-loop structures in pre-miRNA to produce mature miRNAs. Deviation from stem-loop leads to deregulated mature miRNA levels, providing readout of the existence of an alternate structure per se G-quadruplex-mediated structural interference in miRNA maturation. In vitro analysis using beacon and Dicer cleavage assays indicated that mature miRNA levels depend on relative amounts of K+: and Mg2+ ions, suggesting an ion-dependent structural shift. Further in cellulo studies with and without TmPyP4 (RNA G-quadruplex destabilizer) demonstrated that miRNA biogenesis is modulated by G-quadruplex to stem-loop equilibrium in a subset of pre-miRNAs. Our combined analysis thus provides evidence of the formation of noncanonical G-quaciruplexes in competition with canonical stem-loop structure inside the cell and its effect on miRNA maturation in a comprehensive manner.